Moving from the loom to the toothpick: : the school and the Lickanantay identity - Miranda Carvajal, Carlos (2023)
The present work seeks to know how the schooling experience of the Lickanantay community affected the development of their identity as indigenous after being subjected to educational migrations within and outside the ancestral territories. Methodologically, content analysis techniques were used, including ethnographic models at the field and auto-ethnographic analysis level, proposing a decolonial research directly related to the indigenous identity of participants and researchers, observing a position of militant researcher in the social process of vindication of ancestral knowledge. The main conclusion was that the school acted as a control and assimilation device, effects that were intended by the processes of the installation of a unified state.